Carbohydrate loading in female endurance athletes: Effect of menstrual cycle phase - McLay, R.; Thomson, C.; Rehrer, N. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Endurance athletes, both male and female, utilise the nutritional practice of carbohydrate loading (CHO) prior to important events. Investigations in this area are generally restricted to males to avoid the unresolved effects the menstrual cycle may have on endurance exercise; however, evidence is accumulating that gender differences may exist. This study was designed to examine CHO loading in females and th e effect menstrual cycle phase has on substrate utilisation, and performance. Seven trained female cyclists or triathletes (VO2max, 50.9 ± 3.6 ml/min/kg mean ± SD) with regular menstrual cycles and no oral contraceptive use within the previous 6 mo participated in this study. Oral basal body temperature was recorded daily to confirm a biphasic cycle and to identify ovulation (verified by blood sampling). Following depletion exercise (40 km time trial), subjects were provided with either a normal diet (N) (Energy 11986.4 ± 1113.6 KJ; Protein 17.6 ± 2.3 % total energy (TE); CHO 47.2 ± 4.5 %TE; Fat 35 ± 4.5 %TE) or CHO loading diet (C) (Energy 11489.5 ± 966.2 kJ; Protein 14.3 ± 1.4 %TE; CHO 77.2 ± 3.4 %TE; Fat 7.3 ± 1.6 %TE) for three days. On day 4 a cycling test comprising 5 min warm-up, 10 min at 45, 60, and 75% VO2max, each separated and followed by 10 min cycling at 50% VO2max, followed by a 16 km time trial, was performed. A randomised, cross-over design was employed with testing at both mid-follicular and mid-luteal phases. Glycerol, free fatty acids, haematocrit, and haemoglobin in blood, and substrate utilisation, via indirect calorimetry, were measured. No difference in substrate utilisation between phases was observed. Increased CHO oxidation with C was observed at 45% VO2max (R = 0.93 ± 0.02; R = 0.90 ± 0.03 C, N, resp.) at 60% VO2max (R = 0.92 ± 0.02; R = 0.89 ± 0.03) but not at 75% VO2max (R = 0.98 ± 0.03; R = 0.97 ± 0.04). Performance was not affected by menstrual cycle phase nor dietary manipulation. In conclusion, it appears menstrual cycle phase does not influence substrate utilisation during exercise at or below 75% VO2max, nor does it affect performance or substrate utilisation during a 16 km trial. Diet influences substrate utilisation at and below 60% VO2max but not at 75% VO2max (26.2 ± 1.2min). Lack of improvement in performance with CHO loading may be more related to exercise duration or variability in training status and/or small number of subjects rather than an inherent difference in response of females.